PENGEMBANGAN KEWIRAUSAHAAN MAHASISWA DALAM PENGELOLAAN KEUANGAN USAHA BERBASIS APLIKASI - Titi Rahmawati; Anggara Setya Saputra; Harliana Harliana (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
The initial concept of the trilogipreneur is how to provide entrepreneurial stimulus for non-productive community groups, and through Student Based Entrepreneurship service activities, it is hoped that the idea of this trilogipreneur will become a method that provides stimulus for new entrepreneurs as well as a provision for business development for the entrepreneurial ecosystem of groups that move towards a productive economy that is environmentally sound and sustainable by connecting life campus entrepreneurship with the industrial world and regional or national entrepreneurship networks. The purpose of the Student Based Entrepreneurship service program in the trilogipreneur method aims to provide innovative ways and solutions to partner problems including: Socialization, mentoring, and entrepreneurship training with environmental and sustainable insight so that partners have knowledge in developing their business with planning, targets, and business results can be managed properly; Socialization, mentoring, and training in improving financial management skills based on android applications, namely Kledo Accounting Software; Socialization, mentoring, and training in improving skills in human resource management so that production becomes more stable and there is standardization of quality and service as differentiation.